(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-1-123-134 Ivan Bunin and Nikolay Roerich created the concepts about the Ceylon-Indian way of the European peoples, expressed them in the images of uterine brotherhood, cradle and cultural kinship with the ancient civilization. The analysis of philological and historiosophical sources XIX century allowed us to outline two multidirectional trends in solving the Ceylon-Indian question: one of them found its embodiment in linguistic and cultural constructions and in the works of Bunin and Roerich, the other – in statements about European superiority over “backward Eastern humanity” (Fichte, Hegel, Tylor). Key words: Ivan Bunin, Nikolay Roerich, Ceylon, India, Russia, Europe, anthropic memory of the unity of mankind